Zastosowanie wykładników Lapunowa do prognozowania zjawisk ekonomicznych opisanych za pomocą szeregów czasowych - Miśkiewicz, Monika (The application of Lyapunov exponents to the prediction of time series, 2007)
The paper presents the new method of chaotic series prediction. This method is based on a basic characteristic of chaotic systems which is sensitive dependence upon initial conditions (SDUIC). This figures referred to as Lyapunov exponents are a measure of the SDUIC. They measure the rate of the divergence of trajectories in state space. The method involves, first, the reconstruction of a phase space using a time series and then the prediction of unknown phase space point making use of the Lyapunov exponents as a qualitative parameter. As a result of the transformation of this phase space point the predicted time series data can be obtained. Numerical examples have proved that the method is effective.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 211-223